KEPENTINGAN EKONOMI DAN POLITIK MEDIA DALAM RUANG PUBLIK INDONESIA - Meylda Adheista; Isma Nabilah; Muhammad Iqbal (Yayasan Azam Kemajuan Rantau Anak Bengkalis, 2020)
This study aims to find out how the economic and political interests of the media in Indonesia are primarily related to public space in Indonesia. Especially in the 2019 presidential election wherein the capital owners controlled and even participated directly in political circles. The focus of this research is on the criticize of how the media can not be separated from political influence to achieve economic interests. The theory used in this research is the theory of political economy of media and the concept of public space. the paradigm used in this study is critical. The mass media, both print and broadcast (TV and Radio) play a very significant role in disseminating messages that are important to the public / society. Karl Marx states